PENGARUH LATIHAN KOGNISI TERHADAP PERCAYA DIRI ATLET INTELEKTUAL TINGGI PADA CABANG OLAHRAGA OPEN-SKILL - Rudiatna, Muhammad Aditya; Komarudin, Komarudin; Purnamasari, Ira; Novian, Geraldi (Fakultas Ilmu Keolahragaan Unimed, 2024)
This research discusses cognition training (life kinetic and brain gym) on the self-confidence of high intellectual athletes in open-skill sports. This research aimed to determine the effect of cognitive training on the self-confidence of high-intellectual athletes in open-skill sports and to determine the difference in the influence of life kinetic and brain gym training on the self-confidence of high-intellectual athletes in open-skill sports. The method in this research is experimental. The population used was 48 athletes in open-skill sports. The sample consisted of 21 athletes taken using the purposive sampling technique. The data analysis techniques used are the Paired Sample t-test and the Independent Sample t-test. The results of this study show that there is a significant influence between life kinetic and brain gym training on the self-confidence of high intellectual athletes in open-skill sports and there is no significant difference in the influence between life kinetic training and brain gym training on the self-confidence of high intellectual athletes in sports open-skill sports